Payload‐centric autonomy for in‐space robotic assembly of modular space structures. Issue 6 (14th June 2018) - Karumanchi, Sisir; Edelberg, Kyle; Nash, Jeremy; Bergh, Charles; Smith, Russell; Emanuel, Blair; Carlton, Jason; Koehler, John; Kim, Junggon; Mukherjee, Rudranarayan; Kennedy, Brett; Backes, Paul
Abstract: The paper addresses the problem of constructing large space structures (∼100 m) by using autonomous robots to assemble modular components in space. We are motivated by the problem of creating space structures at a scale greater than what is feasible with a single self‐deploying design. We had two goals in this work. The first was to investigate and demonstrate the feasibility of long‐order multitask autonomy. The second was to study the balance between required tolerances in hardware design and robotic autonomy. This paper reports on a payload‐centric autonomy paradigm and presents results from laboratory demonstrations of automated assembly of structures using a multilimbed robotic platform. We present results with deployable 20 lb payloads (1 m trusses) that are robotically assembled to form a 3‐m diameter kinematically closed loop structure to subcentimeter accuracy. The robot uses its limbs to deploy the stowed modular structural components, manipulate them in free space, and assemble them via dual‐arm force control. We report on results and lessons learned from multiple successful end‐to‐end in‐lab demonstrations of autonomous truss assembly with JPL's RoboSimian robot originally developed for the Defense Advanced Research Projects Agency (DARPA). Videos of these demonstrations can be seen athttps://goo.gl/muNLJp (JPL, 2017 ). Each end‐to‐end run took precisely 26 min to execute with very little variance across runs. We present changes/improvements to the RoboSimian system post‐DARPA Robotics Challenge (DRC) (Karumanchi et al., 2016 ). The new architecture has been improved with a focus on scalable autonomy as opposed to semiautonomy as required at the DRC.